This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a b c ∘ C = c a b ∘ F ⟹ ( 1 0 0 a + 1 0 b + c ) × 5 9 + 3 2 = 1 0 0 c + 1 0 a + b . Since the RHS is an integer, the LHS must also be an integer. Then ( 1 0 0 a + 1 0 b + c ) × 5 9 must be an integer and ( 1 0 0 a + 1 0 b + c ) is divisible by 5 hence c = 0 or c = 5 .
When c = 0 ,
( 1 0 0 a + 1 0 b ) × 5 9 + 3 2 1 8 0 a + 1 8 b + 3 2 1 7 0 a + 1 7 b ⟹ a , b = 1 0 a + b = 1 0 a + b = − 3 2 < 0 No solution.
When c = 5 ,
( 1 0 0 a + 1 0 b + 5 ) × 5 9 + 3 2 1 8 0 a + 1 8 b + 9 + 3 2 1 7 0 a + 1 7 b 1 0 a + b ⟹ a b = 5 0 0 + 1 0 a + b = 5 0 0 + 1 0 a + b = 4 5 9 = 2 7 = 2 = 7 Divide both sides by 1 7
Therefore, a + b + c = 2 + 7 + 5 = 1 4 .